Surgical treatment of distal tibia fractures: open versus MIPO - GULABI, Deniz; BEKLER, Halil Ibrahim; SAGLAM, Fevzi; TASDEMIR, Zeki; CECEN, Gultekin Sitki; Elmali, NURZAT; ELMALI, NURZAT (My University, 2016)
BACKGROUND: Treatment of the distal tibial fractures are challenging due to the limited soft tissue, subcutaneous location and poor vascularity. In this control-matched study, it was aimed to compare the traditional open reduction and internal fixation with minimal invasive plating (MIPO). We hypothesized that superior results may be achieved with MIPO technique. METHODS: 22 patients treated with traditional open reduction and internal fixation were matched with 22 patients treated with closed reduction and MIPO on the basis of age (±3), gender, and fracture pattern (AO classification). Evaluation was assed according to the wound problems, the American Orthopaedic Foot and Ankle surgery (AOFAS) scoring, radiological union, malunion, delayed union, hospitalisation time, time from injury to surgery, and operation time. RESULTS: There was no significant difference in the distribution of AO/OTA classification, age, gender, AOFAS score, time from injury to operation, follow-up, bone union time, delayed union, malunion and infection (p>0.05). The operation time was significantly longer in the open group than in the MIPO group: 69.59±7.21 min. for the ORIF, and 61.14±5.61 for the MIPO group (p<0.01).The hospitalisation time was significantly longer in the open group than in the MIPO group: 7.64±4.71 days for the MIPO, and 10.18±4.32 days for the ORIF group (p<0.05). CONCLUSION: MIPO technique can be beneficial for the treatment of distal tibia AO/OTA A and B type fractures with reduced hospital stay, cost-effectiveness, and infection rate.